A Rare Cause of Fungal Rhinosinusitis: Exophiala jeanselmai - Eh Dam, V Sha Kri; Ramli, Ramiza Ramza (International Journal of Human and Health Sciences (IJHHS), 2022)
Fungal rhinosinusitis (FRS) is a rarely encountered disease; however, the incidence is increasing. It has a strong association with the impaired immune system of the host as well as a suitable environment for fungal growth. Fungal spores are abundant in the surroundings and can enter the nasal airway and the paranasal sinuses (PNS) through inhalation; however, only a small number of patients develop FRS. The primary organisms responsible for FRS are Aspergillus sp., Rhizopus sp., and some of the dematiaceous fungi. We present a case of FRS in an immunosuppressed patient caused by scarce fungal species, Exophiala jeanselmai. This rare fungus has never been reported to be associated with FRS before. They are dematiaceous fungi of low virulence and infection are usually restricted to skin and soft tissue. International Journal of Human and Health Sciences Vol. 06 No. 02 April’22 Page: 217-221